2014
DOI: 10.1111/tpj.12572
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale gene expression profiling data for the model moss Physcomitrella patens aid understanding of developmental progression, culture and stress conditions

Abstract: SUMMARYThe moss Physcomitrella patens is an important model organism for studying plant evolution, development, physiology and biotechnology. Here we have generated microarray gene expression data covering the principal developmental stages, culture forms and some environmental/stress conditions. Example analyses of developmental stages and growth conditions as well as abiotic stress treatments demonstrate that (i) growth stage is dominant over culture conditions, (ii) liquid culture is not stressful for the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 46 publications
2
87
1
Order By: Relevance
“…While the morphological details of the moss sporophyte, its developmental time line, and the transcriptional profile are relatively well described (Cove et al, 2009;Vidali and Bezanilla, 2012;Hiss et al, 2014;Scanlon, 2015a, 2015b;Ortiz-Ramirez et al, 2016), the mechanistic details and signal transduction pathways involved during sporophyte formation are largely unknown. Our results provide a clue to the types of proteins that might be involved in the signaling event that takes place during sporophyte formation.…”
Section: Discussionmentioning
confidence: 99%
“…While the morphological details of the moss sporophyte, its developmental time line, and the transcriptional profile are relatively well described (Cove et al, 2009;Vidali and Bezanilla, 2012;Hiss et al, 2014;Scanlon, 2015a, 2015b;Ortiz-Ramirez et al, 2016), the mechanistic details and signal transduction pathways involved during sporophyte formation are largely unknown. Our results provide a clue to the types of proteins that might be involved in the signaling event that takes place during sporophyte formation.…”
Section: Discussionmentioning
confidence: 99%
“…Results include the avoidance of stress by downregulation of photosynthesis (Cuming et al 2007;Hiss et al 2014) and the rapid upregulation of protective mechanism for photosynthesis, membranes and protein folding (Azzabi et al 2012;Hiss et al 2014;Ruibal et al 2013). At the metabolic level, free soluble sugars, such as trehanderose, are accumulated to increase the intracellular osmolarity and counterbalance water-loss (Nagao et al 2005(Nagao et al , 2006.…”
Section: Mosses Employ Several Strategies To Increase Stress Tolerancementioning
confidence: 99%
“…To date, most attention has been paid to the mechanisms by which mosses master the cellular challenges during dehydration/rehydration and freezing, sometimes also employing ABA or salt treatment (Cui et al 2012;Cuming et al 2007;Hiss et al 2014;Nagao et al 2005;Oliver et al 2005). Results include the avoidance of stress by downregulation of photosynthesis (Cuming et al 2007;Hiss et al 2014) and the rapid upregulation of protective mechanism for photosynthesis, membranes and protein folding (Azzabi et al 2012;Hiss et al 2014;Ruibal et al 2013).…”
Section: Mosses Employ Several Strategies To Increase Stress Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…Further, the axenic cultivation of different growth states under highly standardized conditions facilitates reproducible high throughput analysis of proteomes, transcriptomes, and metabolites (35)(36)(37)(38)(39)(40)(41). Recently, we reported that ATE abundance underlies spatiotemporal patterning in the moss Physcomitrella patens using a translational GUS reporter fusion via knock-in at the endogenous genomic locus (11).…”
mentioning
confidence: 99%